Excavations at Chester Medieval and post-Medieval development within the northern and eastern suburbs to c. 1900. - DODD, LEIGH (ARCHAEOPRESS, 2021)
Bringing together results from archaeological investigations carried out in the suburbs to the north and east of the medieval and later City of Chester, significant stretches of the defensive ditch cut during the Civil War of the 17th century were excavated. The results bring into question the accepted lines of these massive defensive outworks.